Optimization and in silico analysis of cold-adapted lipase from an antarctic pseudomonas sp strain AMS8 reaction in Triton X-100 reverse micelles - Abd. Jalil, Fatin Nur Fauzi Ana; Raja Abd. Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Mohamad Ali, Mohd Shukuri (MDPI, 2018)
A moderate yield of a purified enzyme can be achieved by using the simple technique of reverse micellar extraction (RME). RME is a liquid–liquid extraction method that uses a surfactant and an organic solvent to extract biomolecules. Instead of traditional chromatographic purification methods, which are tedious and expensive, RME using the nonionic surfactant Triton X-100 and toluene is used as an alternative purification technique to purify a recombinant cold-adapted lipase, AMS8. Various process parameters were optimized to maximize the activity recovery of the AMS8 lipase. The optimal conditions were found to be 50 mM sodium phosphate buffer, pH 7, 0.125 M NaCl, and 0.07 M Triton X-100 in toluene at 10 °C. Approximately 56% of the lipase activity was successfully recovered. Structural analysis of the lipase in a reverse micelle (RM) was performed using an in silico approach. The predicted model of AMS8 lipase was simulated in the Triton X-100/toluene reverse micelles from 5 to 40 °C. The lid 2 was slightly opened at 10 °C. However, the secondary structure of AMS8 was most affected in the non-catalytic domain compared to the catalytic domain, with an increased coil conformation. These results suggest that an AMS8 lipase can be extracted using Triton X-100/water/toluene micelles at low temperature. This RME approach will be an important tool for the downstream processing of recombinant cold-adapted lipases